Analisis Peran Perdagangan Maritim Terhadap Sejarah Perekonomian ASEAN - Aditya Darma; Ahmad Fakhri Hutauruk; Benny Junior Kaban (Polyscopia, 2024)
Maritime trade is an economic activity carried out through sea routes such as exports and imports, the main function of maritime trade is to improve the economy of a country and the welfare between entrepreneurs, this maritime trade is not only carried out by two countries but can even be between one country and one organization that has members with several countries in it such as ASEAN. The purpose of this study is to provide knowledge about the role of maritime trade in the history of the economy in ASEAN. The results of this study explain the influence of maritime trade on the economic development of ASEAN and ASEAN member states. ASEAN is an organization formed with the aim of improving the economies of the countries in Southeast Asia consisting of Indonesia, Malaysia, Singapore, Thailand, Vietnam, Brunei Darussalam, Cambodia, Philippines, Myanmar, Laos. This study uses qualitative research with a library study approach to research accurate and relevant data so that readers can easily understand the range of knowledge from this research.